Investigation on the mechanical and physical properties of treated and untreated woven sugar-palm fibre reinforced composite - Mohamad Bahtiar, Wahieda (2012)
Natural fibres offer environmental benefits such as biodegradable and can be obtained from renewable resources. In term of strength, natural fibres are still inferior by the synthetic fibres. However, there is lack of investigations done to characterise and compare different types and orientation done on the natural fibres. The basic purpose of the study is to determine the mechanical and physical properties of sugar-palm fibres under various treatment processes, to analyse the performance of mechanical and physical properties of different type of orientations and to compare the obtained properties with other natural fibres. The study starts with preparation of the sugar-palm fibres, followed by surface treatments by alkali and acid solutions and weaving the fibre into a woven fibre before putting it into the mould. After dried, the composite board was cut into specimens and tested for 3-point flexural test and tensile test. Surface morphological analysis by using SEM machine was done before doing the data analysis. The outcome of the study proved that the chemical treated fibres has higher tensile and flexural properties compared to the untreated fibres where the value of tensile stress for alkali treated, acid treated and untreated fibres are 27.92 MPa, 26.41 MPa and 25.75 MPa respectively. In addition, the value of flexural stress for alkali treated, acid treated and untreated fibres are 81.16 MPa, 79.07 MPa and 41.34 MPa respectively. As a conclusion, woven sugar-palm fibre reinforced epoxy composite is appropriate to use as a replacement for the synthetic fibre such as glass and carbon fibre since it has good tensile and flexural properties. With these properties, it is proved that the treated sugarpalm